Analysis of graduates performance based on programme educational objective assessment for an electrical engineering degree / Bibi Norasiqin Sheikh Rahimullah ... [et al.] - Sheikh Rahimullah, Bibi Norasiqin; Mansor, Wahidah; Latip, Mohd Fuad; Mohamad, Hasmaini; Che Abdullah, Syahrul Afzal (Universiti Teknologi MARA, 2020)
Programme Educational Objectives (PEOs) are specific goals that are aligned with the vision and mission of an institution of higher learning. The PEOs describe the expected achievements of the graduates in their career and professional accomplishment after graduation. At Faculty of Electrical Engineering, Universiti Teknologi MARA, Shah Alam, the PEOs of undergraduate programmes are particularly designed to ensure that the graduates are well-equipped with a broad foundation of theoretical and practical knowledge in various electrical engineering areas of interest and to prepare them for the rapidly changing engineering technology. These PEOs are carefully aligned with the vision and mission of the university and faculty and should be achieved by the graduates 3 to 4 years after graduating. These PEOs must be assessed and evaluated to determine the PEOs’ attainment of the programme. Therefore, assessment and evaluation activities must be available to plan and organize the process of obtaining the PEOs’ attainment. Surveys on graduate attributes need to be conducted to gain feedbacks from stakeholders 3 to 4 years after graduation. In this study, anonymous online questionnaire survey was created to obtain the feedbacks from the alumni. These feedbacks are then analysed to assess the PEOs’ attainment. In order to evaluate the performance of the PEOs, performance indicators are developed and used in the evaluation. Outcomes from this study are used to determine the achievement of PEOs and to propose the improvement as part of continuous quality improvement (CQI).